2010
DOI: 10.1038/leu.2010.182
|View full text |Cite
|
Sign up to set email alerts
|

Identification of disease- and therapy-associated proteome changes in the sera of patients with myelodysplastic syndromes and del(5q)

Abstract: Using ProteinChip array technology, which is based on the surface-enhanced laser desorption/ionization time-of-flight mass spectrometry, we performed proteomic analyses on sera from myelodysplastic syndromes (MDSs) patients with an interstitial deletion of the long arm of chromosome 5 (del(5q)) and those from control individuals. One analysis with 80 samples from 29 patients and 51 control subjects resulted in the detection of 61 peak differences. Another analysis with 36 paired-samples from 18 patients collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…The results obtained by 2-DE concerning ITIH4 fragments may be explained by a progressive fragmentation of ITIH4 fragments in the patient group producing smaller fragments (which could not be detected by 2-DE as used in our study); as well as also the possibility of posttranslational modifications. Nevertheless, in light of the observations from RAEB-1, RCMD, and previous literature [17] it seems that ITIH4 alterations could be a marker specific for myelodysplastic syndrome.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results obtained by 2-DE concerning ITIH4 fragments may be explained by a progressive fragmentation of ITIH4 fragments in the patient group producing smaller fragments (which could not be detected by 2-DE as used in our study); as well as also the possibility of posttranslational modifications. Nevertheless, in light of the observations from RAEB-1, RCMD, and previous literature [17] it seems that ITIH4 alterations could be a marker specific for myelodysplastic syndrome.…”
Section: Discussionmentioning
confidence: 92%
“…ITIH4 is a protein involved in acute phase reaction and is considered to be a possible marker of cancer [16]. Its fragments have been found to be potentially associated with MDS [17]; with differences in the fragmentation of ITIH4 having been shown in literature [16,18] and related to several malignant diseases [18-21]. Moreover, changes in the composition or modifications in ITIH4 fragments were observed in our previous proteomic study describing plasma proteome changes in another MDS subgroup – refractory cytopenia with multilineage dysplasia (RCMD) [22].…”
Section: Discussionmentioning
confidence: 99%
“…ITIH4 fragments have been found to be potentially associated with MDS [9]; and several authors have shown differences in the fragmentation of ITIH4 [21,22]. Furthermore, an alternation in ITIH4 fragments has been described in several malignant diseases [22-25].…”
Section: Discussionmentioning
confidence: 99%
“…Complex protein-protein networks reflect the changes at the transcription level, as well as changes induced by protein modifications depending on (patho) physiological conditions in organisms. Posttranslational modifications of proteins including fragmentation or cross-linking are examples of changes detected exclusively by proteomic techniques [8], which may play a crucial role in the development and progression of the disease [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have implicated serum levels of CXCL4 and CXCL7 as potential prognostic markers in MDS (61,62). To determine whether serum levels of CXCL4 and CXCL7 could potentially serve as biomarkers for DAC response, we quantified the serum concentrations of these chemokines by ELISAs in 35 of 40 CMML patients (Supplemental Figure 6).…”
Section: Somatic Mutations Do Not Correlate With Response To Dac In Cmentioning
confidence: 99%